Muatan Pendidikan Karakter Pada Kalimat Bahasa Inggris - Akhmad, Enni (IAIN Sultan Amai Gorontalo, 2015)
This writing discusses about English language lesson that can be used to implement character values on students or learners. English language teaching and learning, since then is considered as a lesson which only teaches the language skills, namely English language, which comes from secular countries. The teachers, generally, have perception that character education only can be implemented through religion lessons. They do not realize that English language also reflects character values that owned by the language users. Its values are reflected on the models of its sentences, for example the discipline value, the politeness and the honest. The sentences models are taken as the sample in this writing is âTensesâ.Â Â